Bibliometric Analysis of Educative Communication Habituation: An Efforts in Shaping the Morals of Learners in Indonesia - Ali Anhar Syi'bul Huda; Dena Sri Anugerah; Ridwan M. Soleh; Afkarul Azmi (Jurnal Pendidikan Islam Indonesia, 2024)
This research was conducted in March 2024 through a search of the Google Scholar database with the title Educational Communication. Specifically, the maximum number of results was 500 articles as a sample, and the publication range was the last 10 years, starting from 2014-2024. Metadata retrieval using the Publish or Perish (PoP) application version 8.12 was then analyzed descriptively based on the year of publication, publication source, researcher productivity, and journal rank. To get an accurate map of research development, PoP data is exported to the PoPCites format, which will then be mapped simply using Excel and Result as RIS. PoPCites data is mapped by researchers, who are entered into the previously created table, and RIS data is analyzed using the VOSViewer (VV) application version 1.6.20. The results showed that the publication of research results on educational communication from 2014-2024 experienced fluctuations, and the largest source of publication was through e-journals, with as many as 406 articles. While the researchers published their research results 4 people, namely Rr. Tutik Sri Hariyati (4 articles), Ratih Kurniasari (15 articles), Hadi Pratomo (4 articles), and Heni Pujiastuti (6 articles). The VV visualization application shows that the development map of educational communication research consists of 5 clusters. Cluster 1 (5 items), cluster (3 item), cluster 3 (2 items), cluster 4 (2 items), and cluster 5 (2 items) with the most research including literature review, Indonesian systematic literature review, and systematic review.